Pengaruh Kelekatan dan Penalaran Moral terhadap Religiusitas Remaja di Desa Pematung Kecamatan Sakra Barat Kabupaten Lombok Timur-NTB - Hadi, Asrul (YASIN, 2025)
Religiosity is a multi-dimensional value that is not only discuss about the problem of human relationship with God but also about his relationship with fellow human beings and social life. Adolescent religiosity influenced by internal factor, that is the nature of every human being to believe in the existence of God and external factors such as parents, family, school, and community. The purpose of this study is to examine the influence of attachment and moral reasoning to adolescent religiosity. The method of this study is quantitative research with research subjects are 110 adolescents aged 15 to 19 years old. Collecting data using three scales include Inventory of Parent and Peer Attachment (IPPA) with reliability 0,765, scale of moral reasoning is based on the theory of moral development Kohlberg with reliability 0,691, and The Centrality of Religiosity Scale (CRS) with reliability 0,801. Data analysis of this study uses multiple linear regression. The results showed jointly attachment and moral reasoning have a significant influence on adolescent religiosity (p = 0,000 < 0,05), while the most dominant influence of them is adolescent attachment to parents.